Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan pada Shopie Paris BC. Yenni Kecamatan Muara Bulian - Ade Jermawinsyah Zebua (Universitas Batanghari Jambi, 2018)
At this time the competition in the business world is felt increasingly competing, along with the increase of similar companies that offer the same product. The purpose of this study is to determine what factors affect the increase in sales volume in Shopie Paris Bc. Yenni in Muara Bulian. The method of analysis is qualitative descriptive. Data collection in this research is using library research and field research. Types of data used in this study are primary and secondary data. Based on the research that Strategis of marketing in an effort to increase sales volume at Shopie Paris Bc. Yenni in Muara Bulian are product strategy, price, promotion, place and people. Sale of Shopie Paris Bc. Yenni in Muara Bulian in 2015 decreased sales by -0.5%, while in 2013 sales at the highest position with a value of 0.2%. It is recommended that Shopie Paris Bc. Yenni in Muara Bulian more attention to the problem of distribution of goods to consumers. For promotional aspects should be more developed again, meaning in addition to MLM promotion method can be done by opening the booth in front of self-service and can provide training to members about how to market the product.